The Development of explosives competencies, training and education in the UK - Wallace, Ian G.; Akhavan, Jacqueline; Murray, S. G.; Hooper, G. (Cranfield University, 2009)
Competent explosives workers in the Armed Forces and in the civil sector are critical to the safe production, testing and use of explosives. Moreover we need competent explosives specialists to combat the challenge from terrorism and clean up the planet from the explosive hazards that are the legacy of past conflicts. Unfortunately many countries are witnessing a significant loss of capability in this area and are looking at ways of replenishing vital expertise. This paper describes the work done in recent years by the authors and others in the UK to establish numbers of people working in the sector and to consider the skills and knowledge required to carry out their work. It outlines the concept of national occupational standards and the framework of professional and vocational qualifications that are available or are being developed for explosives specialists. It also describes some of the educational and e-learning programmes designed to support this initiative. Ultimately the aim is to address the professionalism of all personnel who deal with explosives in order to reduce the incidence and consequence of accidents and maintain national capability.